2017
DOI: 10.1590/2317-1545v39n2169225
|View full text |Cite
|
Sign up to set email alerts
|

Differential incidence of the lemma on seed germination among different Paspalum dilatatum genotypes

Abstract: -Paspalum dilatatum Poir. is a promising perennial summer grass forage for temperate regions, but among other factors, slow stand establishment has hindered its adoption. One of the reasons may be seed dormancy. Intraspecific variability in seed dormancy has been reported in P. dilatatum, but the mechanisms underlying this variability remain unclear. In this paper, we focus on the role of seed external covering structures on germination, particularly the lemma. Seeds of apomictic and sexual biotypes of P. dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
2
12
0
2
Order By: Relevance
“…Paspalum dilatatum Chirú showed the lowest emergence timing and the highest maximum emergence proportions among Paspalum genotypes for both irrigation treatments. This seedling emergence behaviour is congruent with our previous results showing that the seed dormancy of the Chirú biotype is lower than that of other genotypes of P. dilatatum (Glison et al., 2015, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Paspalum dilatatum Chirú showed the lowest emergence timing and the highest maximum emergence proportions among Paspalum genotypes for both irrigation treatments. This seedling emergence behaviour is congruent with our previous results showing that the seed dormancy of the Chirú biotype is lower than that of other genotypes of P. dilatatum (Glison et al., 2015, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In seeds with similar anatomy the leafy glumes have no effect on dormancy or germination (Duclos et al., 2013); however, the hard lemma and palea of the fertile floret may be strongly implicated. Although water intake is restricted by these structures, they allow sufficient imbibition of the caryopsis to trigger germination (Duclos et al., 2013; Gallart et al., 2008; Glison et al., 2017; West & Marousky, 1989). Scarification procedures or a dry storage period can also be applied to obtain seed lots with lower seed dormancy level (Glison et al., 2015, 2017; Maeda et al., 1997; West & Marousky, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate the existence of distinct mechanisms associated with dormancy in the seeds of forage species. Glison et al (2017) found a difference concerning dormancy between Paspalum dilatatum genotypes due to the motto's incidence. Luccas et al (2018) demonstrated that in Urochloa humidicola, dormancy involves the remaining structure of the caryopsis and the increase in the growth potential of the embryo during storage in addition to the gibberellin and abscisic acid (promoter/inhibitor) balance.…”
Section: Resultsmentioning
confidence: 91%